Teaching strategies being used in the social studies department of the La Salle Greenhills High School - Miranda, Minda T. 1948- (1977)
The purpose of the study was to investigate the teaching strategies being used by the social studies teachers of the La Salle Greenhills High School. The study found out that social studies teachers of La Salle Greenhills High School have a marked preference of the lecture method. However, in the teaching-learning situation, the students expect the social studies teacher to relate classroom learning to that of everyday life. It was also significant to note that while content and materials are considered essential in the instructional field, the students are not so much concerned with the instructional areas mentioned. Further probing is encouraged along these aspects. The results of the study were shown through percentages and the Spearman's Correlation Test.
Vita.
Thesis (M.A. Social Studies Education)--University of the Philippines, Diliman.
Keywords: Social sciences -- Study and teaching (Secondary) -- Philippines -- San Juan (Metropolitan Manila); Social science teachers -- Philippines -- San Juan (Metropolitan Manila)